Epigenetic Changes Predisposing to Type 2 Diabetes in Intrauterine Growth Retardation - Liguori, Alice; Puglianiello, Antonella; Germani, Daniela; Deodati, Annalisa; Peschiaroli, Emanuela; Cianfarani, Stefano (Frontiers in Endocrinology, 2010)
Epidemiologic studies have demonstrated an association between intrauterine growth retardation and a greater risk of chronic disease, including coronary heart disease, hypertension, stroke, and type 2 diabetes in adulthood. An adverse intrauterine environment may affect both growth and development of the organism, permanently programming endocrine and metabolic functions. One of the mechanisms of programming is the epigenetic modification of gene promoters involved in the control of key metabolic pathways. The aim of this review is to provide an overview of the experimental evidence showing the effects of early exposure to suboptimal environment on epigenome. The knowledge of the epigenetic markers of programming may allow the identification of susceptible individuals and the design of targeted prevention strategies.